2017
DOI: 10.1002/rcs.1843
|View full text |Cite
|
Sign up to set email alerts
|

Precision and accuracy of imageless navigation versus freehand implantation of total hip arthroplasty: A systematic review and meta‐analysis

Abstract: Background: Total hip arthroplasty (THA) is named the most successful surgical procedure of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
54
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(57 citation statements)
references
References 49 publications
1
54
0
2
Order By: Relevance
“…And values of deviation for cup anteversion were between 3.4 and 5.5 in the navigation group, and between 6.6 and 13.7 in the conventional group. The values of deviation for cup abduction and anteversion in this study were similar or slightly larger than the values in the meta-analysis reported by Snijders et al [18].…”
Section: Discussionsupporting
confidence: 85%
“…And values of deviation for cup anteversion were between 3.4 and 5.5 in the navigation group, and between 6.6 and 13.7 in the conventional group. The values of deviation for cup abduction and anteversion in this study were similar or slightly larger than the values in the meta-analysis reported by Snijders et al [18].…”
Section: Discussionsupporting
confidence: 85%
“…As no differences between robot-assisted and freehand THA were observed in this study, future work may also consider the use of computer navigation systems as these are less costintensive, when compared with robotic arm-assisted THA, and several studies in the literature have demonstrated that computer navigation systems improve component placement. [30][31][32][33] In conclusion, our study suggests that the robot-assisted THA has the potential utility in restoring the native hip geometry with higher accuracy and repeatability than the freehand THA technique. However, as the magnitude of asymmetry in kinematic parameters in all three anatomical planes was comparable between robot-assisted and freehand THA patient groups, this study suggests that, while both robot-assisted and freehand THA have the potential to improve gait symmetry, no differences in gait symmetry at 1-year follow-up existed between both groups.…”
Section: Discussionmentioning
confidence: 63%
“…Lastly, as in vivo kinematics are influenced by multiple factors including patient, implant, and surgical factors, and the sample size for the freehand THA group is small, further study is needed to further elucidate the influences of these parameters on the robotic arm–assisted THA procedure in terms of in vivo kinematics. As no differences between robot‐assisted and freehand THA were observed in this study, future work may also consider the use of computer navigation systems as these are less cost‐intensive, when compared with robotic arm–assisted THA, and several studies in the literature have demonstrated that computer navigation systems improve component placement …”
Section: Discussionmentioning
confidence: 81%
“…During the study they were asked to set up the surgical scene, adjust the infrared camera field of view and acquire a total of 27 points which were displayed one after another and distributed between pelvic anatomical landmarks, the surface of the acetabulum and femoral landmarks. These high amounts of points enabled learning through repetition, since the simulator would only allow the user to progress in the experience as a new point was acquired, visual and audio feedback were displayed after a successful landmark acquisition, allowing users to 1 Plane that divides the body into front and back sections.…”
Section: Discussionmentioning
confidence: 99%